Pro ASP.NET 2.0 Website Programming - Armstrong, Damon (Apress : Imprint: Apress, 2005)
Pro ASP.NET 2.0 Website Programming shows you how to harness the ASP.NET technology to build websites that tackle real business needs. It provides ideas and practices that help reduce maintenance costs, decrease development time, and manage user perception. It discusses not only the technical implementation but the business reasoning behind the ideasusing real business situations, drawn directly from the author's extensive consulting experience. Business application development projects routinely begin with limited resources, tight budgets, and constrained timelines. Many developers respond to this by starting their coding immediately, with the hope of maximizing their time. But it's already been proven that the best way to finish projects on time and under budget is to invest some time up front to make the development project operate more smoothly and efficiently in the long run. With this book, you'll be able to exploit ASP.NET 2.0 to its full potential, and provide your users and customers with websites that are intuitive, secure, and high performing.